Ciclo reprodutivo de Echinaster (Othilia) brasiliensis Müller & Troschel, 1842 (Echinodermata: Asteroidea) na região do Cabo Frio, RJ - Pereira, Andrea Duque (2002)
ln the present study specimens of Echinaster (Othilia) brasiliensis were collected monthly at João Fernandes Beach, Búzios, Brazil, from August 1999 to December 2000. Reproductive cycle was studied using gonad index and histological analysis of gonads. E. (O.) brasiliensis exhibited a continuous reproduction. Histological analysis of gonads showed asynchrony in gametogenesis among the individuals of this population. Small and mesovitellogenic oocytes (60-160μm) were the dominant size-class in all samples. Several size classes of oocytes were found together in may ovaries along the studied period. No spent ovaries were found. Probably, the ovaries were not empty for the recovering. The pyloric caeca did not show an annual cycle. An inverse relationship between gonad and pyloric caeca indices was not evident.